Second-harmonic generation based on double higher-order topological corner states - Jia-Lin Li; Jun-Fang Wu; Chao Li (Results in Physics, 2023)
Topological corner state provides a promising platform for enhancing nonlinear optical effects, since it enables the light highly localized and is topologically protected against defects. Here, we realize second-harmonic generation (SHG) based on the nonlinear interactions between two different type corner modes. These corner modes have ultrahigh Q factors and large modal overlap factor, and match the doubly resonant condition simultaneously, ensuring SHG with high efficiency. These results may expand our understanding of the nonlinear interaction between higher-order corner modes in a more general framework, and can find applications in the fields of topologically-protected imaging and sensing.